Analysis of American Culture in the Film "Tomorrow’s War" from the Perspective of Soft Power - Lu, Chunxiao (Journal of Theory and Practice of Management Science, 2023)
For many years, tangible forces characterized by physical objects such as economy, military strength, and technology have been regarded as important factors in the external exchanges of powerful countries. However, after World War II, with the strengthening of the trend of globalization, culture, an invisible force, played an increasingly prominent role in national development and played an increasingly important role. Thus, Joseph Nye proposed soft power. Among them, movies, as a form of soft power, have become an important means for countries to showcase their own culture and values to the outside world. This article takes the movie "Tomorrow's War" as an example to analyze the embodiment of American culture and values in the movie, and its role in enhancing American soft power.